SISTEM ABSENSI SISWA MENGGUNAKAN FINGERPRINT BERBASIS ARDUINO MEGA 2560: System;Information;School;Fingerprint. - Yeniwati, Desy; Riswan; Nilawati; Trigina (LP2M Universitas Nurdin Hamzah, 2022)
This study aims to design, create and test the attendance system of SMA Dharma Bhakti 4 Jambi City students using Arduino Mega 2560-based Fingerprint. This research was conducted at SMA Dharma Bhakti 4 Jambi City from January to April 2021.This research was conducted using the R and D (Research and Development) method which includes planning, designing, manufacturing and testing tools carried out by making a tool system with input in the form of a Fingerprint Module. Control system with Arduino Mega 2560. Output system in the form of LCD and SMS reports to parents of SMA Dharma Bhakti 4 students in Jambi City. The way this tool works is by identifying the fingerprint pattern of DB 4 High School students during registration and transfer using the Fingerprint Module. The Fingerprint module is activated by a fingerprint then identified. The fingerprint that is read will appear on the LCD and through serial communication with the Arduino, the fingerprint will automatically respond to send a message in the form of an SMS to the parents of students who have been registered in the Arduino module.The test results on the Module reached 100% successfully detecting fingerprints that can record attendance data for SMA Dharma Bhakti 4 Jambi City students at SD CARD and provide SMS reports to their respective parents.